Formation of leather biostability with the use of cationic polyelectrolytes - Kozar, Oksana; Sprynskyy, Myroslav; Hrechanyky, Julia; Okhmat, Olena; Lawinska, Katarzyna; Rosul, Ruslan; Himych, Valentin (Eastern-European Journal of Enterprise Technologies, 2017)
The creation of new preparations with a wide range of biocidal action on the pathogenic microorganisms, long-term protective action and, at the same time, with low toxicity for humans and safe for the environment, is a relevant direction in the development of modern technologies in the production of leather materials. In the present article we report the results of examining the antibacterial properties of leather, modified with a composition of natural minerals (zeolite, montmorillonite) and polyhexamethyleneguanidine hydrochloride (PHMG-HC) – cationic polyelectrolyte. PHMG-HC is related to the biocides with a wide range of antimicrobial action, it provides surfaces that are treated with a long-lasting bactericidal effect (up to 8 months), which is why it is called a unique biocide with prolonged action. However, up to now, the use of PHMG-HC to provide leather materials with anti-bacterial properties has not been explored. The research was conducted using the lining leather, impregnated with the dispersed solutions of zeolite and montmorillonite. The modification of leather with PHMG-HC, the substance included in the register of preparations permitted by the EU, was carried out at the stage of after-tanning processes in the production of leather. We propose to use the preparation as a polyfunctional material that fixes the filling and greasing materials in the dermis structure and simultaneously provides it with antibacterial properties. As a result of research, we established special features of the anti-bacterial properties of leather depending on the treatment of a semi-finished product with the solutions of PHMG-HC at different concentration and the type of mineral filler. It is shown that the examined samples acquire a certain level of biostability when treated with the solution of PHMG-HC at concentration not lower than 2.5 %. It is determined that the structure of natural minerals and their location in the leather dermis affect the degree of absorption of the biocide by a semi-finished product. It was found that the leather materials, modified with PHMG-HC, exert a pronounced bactericidal effect on the bacteria of the genus Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis. Research results demonstrated the possibility of obtaining leather materials with special antibacterial properties when using environmentally safe biocidal preparation (polyhexamethyleneguanidine hydrochloride) and accessible and cheap natural minerals (zeolite, montmorillonite).